Bat RNA viruses employ viral RHIMs orchestrating species-specific cell death programs linked to Z-RNA sensing and ZBP1-RIPK3 signaling - Sanchita Mishra; Disha Jain; Ayushi Amin Dey; Sahana Nagaraja; Mansi Srivastava; Oyahida Khatun; Keerthana Balamurugan; Micky Anand; Avinash Karkada Ashok; Shashank Tripathi; Mahipal Ganji; Sannula Kesavardhana (iScience)
Summary: RHIM is a protein motif facilitating the assembly of large signaling complexes triggering regulated cell death. A few DNA viruses employ viral RHIMs mimicking host RHIMs and counteract cell death by interacting with host RHIM-proteins to alleviate antiviral defenses. Whether RNA viruses operate such viral RHIMs remains unknown. Here, we identified viral RHIMs in Nsp13 of SARS-CoV-2 and other bat RNA viruses, providing the basis for bats as the hosts for their evolution. Nsp13 promoted viral RHIM and RNA-binding channel-dependent cell death. However, Nsp13 viral RHIM is more critical for human cell death than in bat-derived Tb1 Lu cells, suggesting species-specific regulation. Nsp13 showed RHIM-dependent interactions with ZBP1 and RIPK3, forming large complexes and promoting ZBP1-RIPK3 signaling-mediated cell death. Intriguingly, the SARS-CoV-2 genome consisted of Z-RNA-forming segments promoting Nsp13-dependent cell death. Our findings reveal the functional viral RHIMs of bat-originated RNA viruses regulating host cell death associated with ZBP1-RIPK3 signaling, indicating possible mechanisms of cellular damage and cytokine storm in bat-originated RNA virus infections.